Social Support for High School Bullying Victims: A Quantitative Analysis - Harmalis Harmalis; Ekawarna Ekawarna; Hendra Sofyan; Rosmiati Rosmiati (AL-ISHLAH: Jurnal Pendidikan, 2025)
Bullying victimization among adolescents is associated with psychological distress, social withdrawal, and decreased academic performance. Social support is a critical protective factor that can mitigate these negative effects. This study investigates the relationship between perceived social support and bullying victim behavior among high school students in Kerinci Regency, Indonesia. A descriptive quantitative approach was employed with a sample of 278 students selected using stratified random sampling. Data were collected using two validated instruments: the Delaware Bullying Victimization Scale (DBVS) and the Multidimensional Scale of Perceived Social Support (MSPSS). Instrument reliability was confirmed through a pilot study (Cronbach’s α 0.85). Data analysis included descriptive statistics and simple linear regression using SPSS version 29. Findings revealed a significant positive relationship between social support and reduced bullying victim behavior (R = 0.742, p 0.001), with social support accounting for 59.1% of the variance (R² = 0.591). Among the three dimensions of support, family support was perceived as the highest, followed by support from significant others and peers. The results underscore the importance of strengthening social support systems—especially family support—in mitigating the negative effects of bullying. Interventions that involve families, peers, and school staff can enhance the resilience and psychological well-being of students who experience bullying.